Preparation and characterization of nanorods Sb doped CdO films by sol-gel technique - Serbetci, Z.; Gupta, R. K.; Yakuphanoğlu, Fahrettin (Springer, 2012)
Pure and antimony (Sb) doped CdO films were grown using sol-gel spin coating technique. The structural properties of the films were investigated using atomic force microscopy. The structure of CdO film is converted from microrods to nanorods with Sb dopant. The analysis of optical absorption revealed that optical bandgap of the films changes with doping. The optical bandgap for 0.1, 0.5, 1.0, and 2.0% Sb doped CdO was determined to be 2.28, 2.30, 2.56, and 2.42 eV, respectively. Other optical constants such as refractive index, extinction coefficient, and dielectric constants were calculated using the optical data. The refractive index dispersion of the films obeys the single oscillator model. The volume and surface energy loss functions were calculated and observed to increase with increase in the photon energy.
Keywords: CdO; Antimony; Sol-gel; Bandgap; Optical constant